Detection of Otosclerosis-Specific Measles Virus Receptor (Cd46) Protein Isoforms. (20th June 2013) - Liktor, Balázs; Csomor, Péter; Karosi, Tamás
Abstract : Genetic predisposition of otosclerosis has long been suspected, but unclarified. Unique coexpression pattern of measles virus receptor (CD46) splicing isoforms in the human otic capsule is assumed, since otosclerosis is a measles virus-associated organ-specific disease. In order to identify CD46 involved in the pathogenesis of otosclerosis, we used representative groups of histologically diagnosed otosclerotic, nonotosclerotic, and normal stapes footplates( n = 109 ) . Consecutive histopathological examinations and CD46-specific Western blot analysis were performed. Normal and nonotosclerotic stapes footplates showed consistent expression of the conventional c, d, e, f, and l CD46 isoforms. In contrast, four novel isoforms (os1–4) translated as intact proteins were additionally detected in each otosclerotic specimen. The study herein presented provides evidence for the otosclerosis-associated expression pattern of CD46. This finding might explain the organ-specific, virus-associated and autoimmune-inflammatory pathogenesis of otosclerosis. Regarding our current knowledge, this is the first report that confirms the presence of four new disease-specific protein variants of CD46.